ANALISIS FAKTOR KONFIRMATORI ASPEK LITERASI MATEMATIK DALAM PROSES PEMECAHAN MASALAH - Ria Noviana Agus; Rina Oktaviyanthi; Yani Supriani (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
The students’ mathematical literacy is a students’ skill in mathematics that become the initial support to enhance several potential cognitive skill i.e. analysis, synthesis, evaluation and students’ decision making in mathematics. The purpose of this study was to identify mathematical literacy aspects that develops in the students’ problem solving process. Participants of this study were 50 students in Calculus class at Universitas Serang Raya. The mathematical literacy aspects used is the relationship between the mathematical process (3 categories) and the basic mathematics skill (7 categories). The identification of a number variables of mathematical literacy that developed in the students’ problem solving process traced by confirmatory factor analysis. The analytical procedure obtained that three factors of mathematical literacy that supported the development of students’ problem solving work namely reasoning, devising strategies and mathematising. The dominant factor that provides a huge impact is the reasoning with the diversity data fairly accurate 74,31%. These results can be taken into consideration in preparing instructional and evaluations materials particularly in Calculus and as a reference analysis as well to similar aspects for other sciences course.Keywords: Confirmatory Factor, Factor Analysis, Mathematical Literacy, Problem Solving